FENOMENA KEMATIAN BAYI DI DUSUN MUNTIGUNUNG, KARANGASEM, BALI, 2013 - Kurniati, Yuli; Septarini, Wayan; Nopiyani, Sri; Putra, Artawan Eka; Wulandari, Lila (ARCHIVE OF COMMUNITY HEALTH; Vol 2 No 2 (2013): Desember (2013))
The target to decrease Infant Mortality Rate (IMR) is one of the goals of the Millennium Development Goals (MDG`s) in 2015. Muntigunung`s village has a relatively high infant mortality rate (29.4 / 1,000 live births) compared by the infant mortality rate of Bali Province (8.19/1,000 live births). The area also have geographical conditions and different socio-cultural community with the surrounding area in Bali, so a more specific approach is required in handling the problems in the area. A qualitative study is needed to explore the factors underlying these conditions. The purpose of this study is to examine the behavior of mothers in Cangkeng Hamlet, Muntigunung in prenatal care practice, childbirth and puerperium. This study used the Rapid Assessment Procedure approach. The qualitative method was used in this study by interviewing 24 women participants and 10 man pasticipants. Participants were selected using purposive technique. The information gathered was analyzed using thematic analysis, and used triangulation of resources and method. The results of this study indicate that prenatal care, childbirth process and post-partum care in Cangkeng is still far from clean and safe criteria. Low education levels, lack of knowledge, negative attitudes towards health care, supernatural perception in the healthy concept of illness, difficult access, mother in-laws influence and lack of husband's role to be underlying conditions of infant morbidity and mortality in this region. This study suggests the existence of a partnership between goverment, NGOs or academic institutions in an effort to closer access to the health services such as forming “Posyandu” in this group;  increase knowledge about reproductive health (prenatal care, early sign of pregnancy, clean and save delivery, and infant care)  for  mother and husband.
Keywords: childbirth, self delivery, infant mortality rate, Muntigunung